VD_FINDINFO HC / 2016 / 33 vom 17. November 2015 - VD Tribunal cantonal (2015)
DIVORCE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE | 125 CC, 106 al. 2 CPC (CH), 308 al. 1 let. a CPC (CH), 317 al. 2 CPC (CH), 58 al. 1 CPC (CH), 58 al. 2 CPC (CH)